THE EFFECT OF THE USE OF QRIS DIGITAL PAYMENTS ON THE PURCHASE DECISION OF BUSINESS ADMINISTRATION STUDENTS OF SANGGA BUANA UNIVERSITY YPKP BANDUNG - Barick Ahmad Setiawan; Yuyu Yunengsih; Karmilah Karmilah; Audita Setiawan; Hersusetiyati Hersusetiyati (Multifinance, 2025)
This study was conducted to determine the effect of the use of QRIS digital payments on purchasing decisions at Business Administration Students of Sangga Buana University YPKP Bandung. The purpose of this study was to determine how much influence it has. This study uses a quantitative method with a descriptive associative research type, sampling was carried out using a non-probability sampling method with a simple random sampling type. The number of relevant respondents according to the criteria was 97 people. The data analysis techniques used were descriptive analysis and simple linear regression analysis. The results of the simple regression analysis obtained a constant number value of 22.642 while the regression coefficient value was 0.330, so it can be interpreted that the constant value of the QRIS digital payment variable is 0 (constant), and the purchasing decision variable is 22.642. The regression coefficient value says that the QRIS digital payment variable has a positive influence on the purchasing decision variable. The magnitude of the influence of QRIS digital payments on purchasing decisions is 19.7%, it can be interpreted that as much as 19.7% of the purchasing decisions of Sangga Buana University YPKP Bandung students are influenced by QRIS digital payments.